2021
DOI: 10.1038/s41598-021-89409-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduced competence to arboviruses following the sustainable invasion of Wolbachia into native Aedes aegypti from Southeastern Brazil

Abstract: Field release of Wolbachia-infected Aedes aegypti has emerged as a promising solution to manage the transmission of dengue, Zika and chikungunya in endemic areas across the globe. Through an efficient self-dispersing mechanism, and the ability to induce virus-blocking properties, Wolbachia offers an unmatched potential to gradually modify wild Ae. aegypti populations turning them unsuitable disease vectors. Here we describe a proof-of-concept field trial carried out in a small community of Niterói, greater Rio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 69 publications
1
34
0
Order By: Relevance
“…Corroborating the Australian findings, recent trials in Indonesia ( Tantowijoyo et al, 2020 ) and Southeastern Brazil ( Garcia et al, 2019 ; Gesto et al, 2021 ) have also reported the successful invasion and establishment of w Mel at some localities, with preliminary evidence of arboviral disease reduction ( Durovni et al, 2020 ; Indriani et al, 2020 ; Pinto et al, 2021 ). In the particular context of Southeastern Brazil, trials have initially targeted small neighborhoods of Rio de Janeiro and the nearby city Niterói, following adult ( Garcia et al, 2019 ) or egg deployment methods ( Gesto et al, 2021 ). With high w Mel frequencies, and DENV and ZIKV refractoriness maintained intact over the post-release period ( Gesto et al, 2021 ), additional areas of both cities could be considered for Wolbachia implementation.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Corroborating the Australian findings, recent trials in Indonesia ( Tantowijoyo et al, 2020 ) and Southeastern Brazil ( Garcia et al, 2019 ; Gesto et al, 2021 ) have also reported the successful invasion and establishment of w Mel at some localities, with preliminary evidence of arboviral disease reduction ( Durovni et al, 2020 ; Indriani et al, 2020 ; Pinto et al, 2021 ). In the particular context of Southeastern Brazil, trials have initially targeted small neighborhoods of Rio de Janeiro and the nearby city Niterói, following adult ( Garcia et al, 2019 ) or egg deployment methods ( Gesto et al, 2021 ). With high w Mel frequencies, and DENV and ZIKV refractoriness maintained intact over the post-release period ( Gesto et al, 2021 ), additional areas of both cities could be considered for Wolbachia implementation.…”
Section: Introductionmentioning
confidence: 81%
“…In the particular context of Southeastern Brazil, trials have initially targeted small neighborhoods of Rio de Janeiro and the nearby city Niterói, following adult ( Garcia et al, 2019 ) or egg deployment methods ( Gesto et al, 2021 ). With high w Mel frequencies, and DENV and ZIKV refractoriness maintained intact over the post-release period ( Gesto et al, 2021 ), additional areas of both cities could be considered for Wolbachia implementation.…”
Section: Introductionmentioning
confidence: 99%
“…A likely contributing factor is that these scaled deployments have largely used adult mosquitoes released from vehicles, which does not deliver as spatially homogeneous a deployment as occurred previously in Indonesia and Australia. In contrast, the small-scale pilot releases in the Jurujuba neighbourhood of Niterói in 2015 achieved rapid and sustained introgression of wMel after 8-31 weeks of egg-based releases [20]. Additionally, Niterói release areas were complex urban environments with high rise areas and large informal settlements, where field activities were frequently interrupted by security issues and where physical barriers to spread [30], spatial heterogeneity in mosquito abundance [31], and limited mosquito dispersal [32] could have contributed to slower wMel introgression.…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 91%
“…aegypti line described in Garcia et al 2019 [23] was used for releases. The wMel-infected lines were maintained in controlled laboratory conditions, in 900 Release zone 1 includes the Jurujuba neighbourhood where pilot releases were conducted in 2015-16 [20], for all metrics except 'Estimated mosquitoes released' which includes only the expanded releases in zone 1 beginning in February 2017; the month that BG traps were first installed in zone 1 also excludes the pilot release period.…”
Section: Mosquito Productionmentioning
confidence: 99%
See 1 more Smart Citation